2017
DOI: 10.3997/2214-4609.201702026
|View full text |Cite
|
Sign up to set email alerts
|

Re-parameterization of the Cole-Cole Model for Improved Spectral Inversion of Induced Polarization Data

Abstract: The induced polarization phenomenon, both in time domain and frequency domain, is often parameterised using the empirical Cole–Cole model. To improve the resolution of model parameters and to decrease the parameter correlations in the inversion process of induced polarization data, we suggest here three re‐parameterisations of the Cole–Cole model, namely the maximum phase angle Cole–Cole model, the maximum imaginary conductivity Cole–Cole model, and the minimum imaginary resistivity Cole–Cole model. The maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 36 publications
(63 reference statements)
0
35
0
Order By: Relevance
“…The Cole‐Cole model in its conductivity form is expressed as (e.g., Tarasov & Titov, ) σ|f=σ0[]|1+m01m0|111+|i2πfτσC where σ is the complex conductivity, σ0 is the DC conductivity, m0 is the intrinsic chargeability, τσ is the relaxation time, C is the frequency exponent, f is the frequency, and i is the imaginary unit. In equation , the m0 and C parameters are strongly correlated, and thus poorly resolved in the inversion (Fiandaca et al, ). In order to reduce the parameter correlation, and hence improve the inversion results, Fiandaca et al () introduced the maximum imaginary conductivity (MIC) model, in which m0 is replaced by maximum imaginary conductivity σmax of the Cole‐Cole spectrum (Figure ) and the model space italicmitalicMitalicIitalicC becomes italicmitalicMitalicIitalicC= {}|σ0,σmax, τσ, C …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cole‐Cole model in its conductivity form is expressed as (e.g., Tarasov & Titov, ) σ|f=σ0[]|1+m01m0|111+|i2πfτσC where σ is the complex conductivity, σ0 is the DC conductivity, m0 is the intrinsic chargeability, τσ is the relaxation time, C is the frequency exponent, f is the frequency, and i is the imaginary unit. In equation , the m0 and C parameters are strongly correlated, and thus poorly resolved in the inversion (Fiandaca et al, ). In order to reduce the parameter correlation, and hence improve the inversion results, Fiandaca et al () introduced the maximum imaginary conductivity (MIC) model, in which m0 is replaced by maximum imaginary conductivity σmax of the Cole‐Cole spectrum (Figure ) and the model space italicmitalicMitalicIitalicC becomes italicmitalicMitalicIitalicC= {}|σ0,σmax, τσ, C …”
Section: Methodsmentioning
confidence: 99%
“…In equation , the m0 and C parameters are strongly correlated, and thus poorly resolved in the inversion (Fiandaca et al, ). In order to reduce the parameter correlation, and hence improve the inversion results, Fiandaca et al () introduced the maximum imaginary conductivity (MIC) model, in which m0 is replaced by maximum imaginary conductivity σmax of the Cole‐Cole spectrum (Figure ) and the model space italicmitalicMitalicIitalicC becomes italicmitalicMitalicIitalicC= {}|σ0,σmax, τσ, C …”
Section: Methodsmentioning
confidence: 99%
“…63 ′ determined from multisalinity resistivity measurements and Furthermore, Weller et al (2013) found that the salinity dependency of the real surface 146 conductivity parallels the salinity dependency of the imaginary surface conductivity, which can be 147 expressed as (Weller et al, 2011;Weller et al, 2015): 148 where * is the complex conductivity, 0 is the DC conductivity, 0 is the intrinsic chargeability, 182 is the relaxation time, is the frequency exponent, is the frequency and is the imaginary 183 unit. Using MCMC (Monte Carlo Markov Chain) analysis, Fiandaca et al (2017a) (Fig. 1b).…”
mentioning
confidence: 99%
“…We consider the MPA to be the simplest parameter, which can describe the amplitude of polarization in a comparable manner for all samples. It can be obtained directly from any phase spectrum and can also be inverted from field time domain IP measurements (Fiandaca et al, ; Madsen et al, ). We calculate the MPA, based on the phase angle value at the summit of spectral peaks (Figure ), if a clear peak is observed in the phase spectrum, or the average phase angle of a linear/flat section when that is observed (e.g., L75).…”
Section: Resultsmentioning
confidence: 99%
“…The peak frequency at which the MPA is reached, is, however, missing in this description. Since it is a more complicated and ambiguous parameter to calculate, both in field and in time domain IP studies, we do not analyze it quantitatively here (Fiandaca et al, ; Maurya et al, ).…”
Section: Resultsmentioning
confidence: 99%